Audiovisual resources at university teachers. The use of videoblog as communication tool. - García Montero, Eva; Rodríguez-Carmona, Laura Melendo; Presol Herrero, África (Historia y Comunicación Social, 2014)
The following text describes the application of new technologies in the development of university teaching. Specifically in the faculty of communication in UCJC was launched two initiatives in Advertising and Public Relations degree in which students had to use the videoblog as a communication tool.
Keywords: Videoblog; communication; university; advertising; teaching resource.